Mineral nutrition of livestock [ - Suttle, Neville F. (Wallingford, Oxfordshire, UK : CABI, 2010)
The fourth edition of this important book covers the advances in livestock mineral nutrition, updated with more illustrations and additional material on the relationship between livestock and man. Recent developments are discussed, such as increasing th'mineral value' of feeds by the use of additives and enhancing mineral availability through the use of organic sources of trace elements. The concept of the 'mineral footprint' of livestock production is introduced and methods of mineral feeding that lower environmental pollution are presented. Opportunities and problems in manipulating the mineral content of livestock to improve the mineral status of consumers are also addressed. The book is an essential resource for researchers and students in animal nutrition, agriculture and veterinary medicine, and a useful reference for those concerned with human nutrition and environmental protection.
Includes bibliographical references and index
Keywords: Livestock -- Nutrients -- Minerals; Minerals in animal nutrition